Influence of the Common Agricultural Policy on the farmer’s intended decision on water use - Giannoccaro, G.; Berbel, J. (Spanish Journal of Agricultural Research, 2011)
This work is the result of the research under CAP-IRE (Common Agricultural Policies on Rural Economies) project where the effects of post 2013 CAP scenarios are investigated. The broad objective is the understanding of farmer’s reactions under CAP scenarios taking into account a long-term perspective by 2020. The analysis is based on 1,328 observations of household farmers across 11 case study regions in nine EU countries. The stated responses are analyzed in order to stress the influence of the next CAP reform on the farmer’s decision process of using more or less water resources on-farm. For this purpose the farmer’s responses to the CAP reforms are analyzed by a logistic model regression. According to the results, farmer’s behaviour would be slightly influenced by the CAP reform. However, significant regional differences are found according to the model regressions. Indeed, in the case of new member states, farmers would have a greater intention to decrease water use if the current CAP support was abolished. Yet factors such as the amount of CAP supports, farmland size, crop specialization, farmer’s age and altitude, are significant determinants of reaction to the CAP reforms. Taking into account the depicted influence on water use opportunities for re-addressing next policy design emerge.